VACCINATION OF CHILDREN WITH SEVERE CHRONIC DISEASES. ALGORITHM FOR THE IMMUNOLOGIST PHYSICIAN - M.V. Fedoseenko; M.G. Galitskaya; L.S. Namazova-Baranova (Union of pediatricians of Russia, 2010)
An annual growth in the number of children with chronic pathologies is registered in the Russian Federation, as in the rest of the world. The disease universe is dominated by visceral, metabolic and motor function disorders. Despite the efforts to enhance healthcare services to children with severe pathologies, the issue of immunization against infections remains unresolved. There is currently an especially strong need to create robust individual immunity against managed infections for patients with chronic pathology, most of whom continue to be socially active. The key principle of the WHO's Expanded Programme of Immunization for such patients is priority immunization. Children with severe chronic pathologies are vaccinated by an individual algorithm in several stages. Key words: vaccinal prevention, severe chronic pathologies, immunization. (Pediatric Pharmacology. - 2010; 7(6):16-21)